Pertanggungjawaban Pidana terhadap Pelaku Tindak Pidana yang Memiliki Gangguan Kepribadian: Studi Putusan Nomor: 414/Pid.Sus/2024/PN.Mjk - Kartika Alfiana; Sanusi Sanusi (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study aims to analyze the criminal liability of perpetrators with personality disorders and assess the judge's considerations in the verdict. The research method used is normative juridical with a doctrinal approach through a literature study of laws and regulations, court decisions, and legal and forensic psychiatric literature. The results of this study indicate that the perpetrator was diagnosed with an emotionally unstable personality disorder of the impulsive type and an adjustment disorder, but was still declared capable of being responsible and sentenced to 4 (four) years in prison. The judge's considerations have not fully integrated the results of the forensic psychiatric examination, so that integrated regulations are needed with a legal and forensic psychiatric approach to achieve a more proportional and just verdict.